Blister-free ion beam patterning of supported graphene. (29th December 2016) - Herbig, Charlotte; Åhlgren, E Harriet; Michely, Thomas
Abstract: Ion irradiation of metal supported two-dimensional layers results over a broad parameter space in noble gas trapping at the interface of the two-dimensional layer and the metal substrate. Trapping may give rise to the formation of gas filled blisters which deteriorate the structural and electronic properties of graphene. Here, we investigate the dependence of noble gas trapping at a graphene/Ir(111) interface and of graphene sputtering on the angle of incidence using scanning tunneling microscopy. Our experimental results are compared to dedicated molecular dynamics simulations. We find that at large impact angles of ≈ 80 ° graphene can be eroded without noble gas trapping and thereby establish conditions for nanopatterning without concomitant blister formation.